Pengaruh Brand Image, Persepsi Harga dan Kualitas Produk Terhadap Keputusan Pembelian Dengan Pelayanan After Sales Sebagai Variabel Moderasi (Studi Kasus Pembelian Sepeda Motor Matic Merek Honda di Jabodetabek) - Putra, Rangga Asmawi; Mutmainah, Isbandriyati; Putra, Mulyana Gustira (Jurnal EMT KITA, 2025)
This study aims to analyze the effect of brand image, price perception and product quality on purchasing decisions with after sales service as a moderating variable. The population in this study were people who had bought and used Honda brand motorbikes in Jabodetabek and the total sample used was 96 respondents. The sampling method used is cluster random sampling and hypothesis testing using moderation regression analysis method. The results of this study indicate that Price Perception and Product Quality has a significant effect on Purchasing Decisions. Brand Image and After Sales Service has no significant effect on Purchasing Decisions. After Sales Service moderates the effect of Price Perception and Product Quality on Purchasing Decisions, After Sales Service does not moderate Brand Image on Purchasing Decisions. The result of the F test show that Brand Image, Price Perception, and Product Quality simultaneously have a significant effect on Purchasing Decisions.